2015
DOI: 10.1089/cell.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Characterization of Bovine Induced Pluripotent Stem Cells by Transposon-Mediated Reprogramming

Abstract: Induced pluripotent stem cells (iPSCs) are a seminal breakthrough in stem cell research and are promising tools for advanced regenerative therapies in humans and reproductive biotechnology in farm animals. iPSCs are particularly valuable in species in which authentic embryonic stem cell (ESC) lines are yet not available. Here, we describe a nonviral method for the derivation of bovine iPSCs employing Sleeping Beauty (SB) and piggyBac (PB) transposon systems encoding different combinations of reprogramming fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 73 publications
2
66
0
Order By: Relevance
“…ESCs and iPSCs are obtained from many animal species: bovine (Bogliotti et al, 2018;Han et al, 2011;Talluri et al, 2015); swine (Chakritbudsabong et al, 2017;Ezashi et al, 2009;Siriboon et al, 2015); horses (Quattrocelli et al, 2016;Tecirlioglu & Trounson, 2007);…”
Section: Species-specific Induced Pluripotent Stem Cell and Embryonmentioning
confidence: 99%
“…ESCs and iPSCs are obtained from many animal species: bovine (Bogliotti et al, 2018;Han et al, 2011;Talluri et al, 2015); swine (Chakritbudsabong et al, 2017;Ezashi et al, 2009;Siriboon et al, 2015); horses (Quattrocelli et al, 2016;Tecirlioglu & Trounson, 2007);…”
Section: Species-specific Induced Pluripotent Stem Cell and Embryonmentioning
confidence: 99%
“…Relative to the embryonic stem cell lines, studies on iPSCs in large animals has made more progress, especially for pigs. However, there are still some difficulties, cell propagation is dependent on exogenous genes and cannot produce germline chimeric offspring [59,127,130,164,165] . These problems need to be solved urgently for the study of PSCs in large animals.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…107 Both SB-and PB-based transposons have been employed to express these reprogramming factors and successfully reprogram mouse, [108][109][110] bovine, 111,112 porcine, 113 and human 110,114,115 fibroblasts into iPS cells. Direct comparative analysis between hyPBase-and SB100X-mediated gene transfer showed that both systems displayed comparable reprogramming efficiency.…”
Section: Hscmentioning
confidence: 99%